2000
DOI: 10.1086/303054
|View full text |Cite
|
Sign up to set email alerts
|

Tightly Clustered 11q23 and 22q11 Breakpoints Permit PCR-Based Detection of the Recurrent Constitutional t(11;22)

Abstract: Palindromic AT-rich repeats (PATRRs) on chromosomes 11q23 and 22q11 at the constitutional t(11;22) breakpoint are predicted to induce genomic instability, which mediates the translocation. A PCR-based translocation-detection system for the t(11;22) has been developed with PCR primers flanking the PATRRs of both chromosomes, to examine the involvement of the PATRRs in the recurrent rearrangement. Forty unrelated carriers of the t(11;22) balanced translocation, plus two additional, independent cases with the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 11 publications
7
79
0
Order By: Relevance
“…We have often observed strand separation of the PATRR fragment even at 37°C. 2 The temperature-induced drop in cruciform formation might be attributed to the competition for superhelix energy release, taking place between cruciform and open regions within the premelting range. We previously reported that only meiotic cells undergo this translocation (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have often observed strand separation of the PATRR fragment even at 37°C. 2 The temperature-induced drop in cruciform formation might be attributed to the competition for superhelix energy release, taking place between cruciform and open regions within the premelting range. We previously reported that only meiotic cells undergo this translocation (7).…”
Section: Discussionmentioning
confidence: 99%
“…We have analyzed only one case of a de novo t(11;22), and it indicated an origin in the paternal germ line. 2 Thus, it is not unreasonable to imagine that PATRR-mediated translocations might occur only in male meiotic cells generated at a lower body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, some smaller deletions are likely to occur through different mechanisms; for example, chromosome recombinations can be mediated by palindromic AT-rich repeats, low copy repeats or olfactory receptor gene clusters. [8][9][10] Consequently, there are likely to be multiple mechanisms that result in the generation of deletions in long arm of chromosome 11.…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed characterization of the junction involved further revealed remnants of DSBs at the center of the two PATRRs, followed by repair through the non-homologous end joining pathway. [29][30][31][32] Two unrelated constitutional t(17;22)(q11;q11) translocations associated with NF1 disease have been reported. 33,34 These two translocations disrupt the NF1 gene on 17q11, which produces the NF1 phenotype in the affected patients.…”
Section: Mechanism Of Chromosomal Abnormalitiesmentioning
confidence: 99%
“…We thereby successfully amplified the der(11) and der(22) junction fragments of balanced t(11;22) carriers as well as the der(22) of patients with Emanuel syndrome. 29 Translocation-specific PCR was then performed using conditions that would allow for the detection of a single molecule of the target DNA. When DNA derived from sperm samples obtained from healthy male volunteers was amplified using our assay, we obtained both positive and negative PCR results, indicating that we had successfully detected translocation products that were de novo in origin (Figure 2d).…”
Section: The Dimorphic Features Of Gcrmentioning
confidence: 99%